life course and development of personality of the great Chinese writer Pu Songling - Nurzhayeva, A. M.; Abdraimova, N. B. (Journal of Oriental Studies, 2016)
this article describes the stages of life of the Chinese writer Pu songling, the formation of his identity as a writer and a man. the importance of his father in the life of the writer was shown, briefly discussed the ideas that influenced the development of psycho-social and intellectual growth of the writer, which subsequently reflected in the work of Pu songling and determined his unique literary style.